The integration of information in a digital, multi-modal learning environment. (February 2019) - Schüler, Anne
Abstract: The aim of the reported eye-tracking study was to investigate whether learners integrate information presented on several pages within a digital learning environment and whether the underlying processes differ between a purely text-based and a multi-modal digital learning environment. Participants ( N  = 97) learned about the development of tornados. Picture presentation (yes vs. no) and presentation of inconsistent information between pages (yes vs. no) was varied between-subjects. Results showed that inconsistent information led to more intense gaze behavior. This indicates that learners re-activated information presented on previous pages to integrate it with the actual information, enabling them to detect the inconsistencies. Furthermore, the data pattern for text-related gaze behavior was not influenced by picture presentation, indicating that cognitive processes in purely text based or multi-modal learning environments are much the same. Comprehension outcomes did not differ between groups. The implications of these results are discussed. Highlights: Gaze behavior was measured during learning within a digital multi-modal environment. The experimental group received information inconsistent to the preceding pages. Inconsistent information changed learners' gaze behavior. Picture presentation did not influence processing of inconsistent information. These findings indicate that information is integrated in multi-modal environments.